Management of chronic traumatic ulcer mimicking oral squamous cell carcinoma on the tongue - Revi Nelonda; Riani Setiadhi (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Traumatic ulcers represent the most common oral mucosal lesions that can be differentiated from oral squamous cell carcinoma (OSCC) by their clinical appearance. From a clinical perspective, OSCC may resemble a chronic traumatic ulcer (CTU) because the base of the CTU that is healing is filled with reddish-pink granulated tissue, similar to that in OSCC. Purpose: The aim of this case report is to provide information about the oral management of a CTU case that imitates OSCC. Case: A 30-year old female presented with a major, painful, non-healing ulcer located on the right lateral of the tongue for the previous two months. Approximately two years before, she had experienced a similar lesion on the tongue. Intra oral examination showed a 10mm x 5mm yellowish ulcer with a fibrous center, erythematous irregular-induration margin and concave yellow base. The 15th, 44th and 47th teeth were sharp and on occlusion caused trauma to the right lateral border of the tongue. Case management: Based on the clinical features, the lesion was imitating OSCC. After a case history review, clinical examination and appropriate investigation, the patient was diagnosed as suffering from a chronic traumatic ulcer. The primary treatment of traumatic ulcers involves eliminating etiological factors. As pharmacological therapy, a mixture of triamcinolone acetonide and 1mg dexamethasone tablet was administered in addition to folic acid and vitamin B12. Conclusion: Clinical presentation of traumatic lesions varies significantly and may, at times, be ambigous. It is important to immediately establish a correct diagnosis and implement prompt treatment of CTU lesions because they play a role at the oral carcinogenesis promotion stage.